THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE MINDS OF YOUNG PEOPLE - Berdiqulova M. E; Toshboyeva B. J (TADQIQOTLAR, 2026)
Annotation  This  article  analyzes  the  role  of  rapidly  developing  digital  technologies,  particularly artificial intelligence, in modern human life. It focuses on the impact of excessive use  of the Internet and digital gadgets on young people’s thinking abilities, learning motivation, and  psychological activity. The advantages and disadvantages of using artificial intelligence in  the  education system  are  discussed  based on  foreign experiences.  In  addition,  the  article  examines  the    competition  between  artificial intelligence and human intelligence, as well as its influence on the  labor market. The study  emphasizes  the  importance  of  maintaininga  balance  between  technological development  and  natural  intelligence,  highlighting  the  need  for  conscious  and purposeful use of digital technologies to ensure intellectual growth and professional development  in the digital era.